2014
DOI: 10.3892/ijo.2014.2655
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel in combination with cetuximab exerts antitumor effect by suppressing NF-κB activity in human oral squamous cell carcinoma cell lines

Abstract: Abstract. In the present study, we examined the antitumor effect of paclitaxel (PTX) in combination with cetuximab in oral squamous cell carcinoma (OSCC) and the mechanism of its enhanced antitumor activity. Treatment of OSCC (HSC2, HSC3 and HSC4) cells with PTX (0.02 µg/ml) and cetuximab (1 µg/ml) combination resulted in a significant inhibition of cell growth in vitro compared to either agent alone. Moreover, it was found by Hoechst 33258 staining that DNA fragmentation markedly occurred in OSCC cells treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…All mice had measurable tumor two weeks after OE19 cell injection. The mice were then randomly grouped (n = 5 per group) and treated intraperitoneally as described earlier with vehicle, paclitaxel (20 mg/kg, 2 times a week for 2 weeks) [ 25 ] or carboplatin (50 mg/kg, 2 times a week for 2 weeks) [ 26 ]. Subcutaneous tumor size was measured twice a week for two weeks and TV with RTV was calculated as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…All mice had measurable tumor two weeks after OE19 cell injection. The mice were then randomly grouped (n = 5 per group) and treated intraperitoneally as described earlier with vehicle, paclitaxel (20 mg/kg, 2 times a week for 2 weeks) [ 25 ] or carboplatin (50 mg/kg, 2 times a week for 2 weeks) [ 26 ]. Subcutaneous tumor size was measured twice a week for two weeks and TV with RTV was calculated as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…As preclinical studies have shown that the combination of cetuximab (Cmab) and taxanes seems to be synergistic (10, 11), paclitaxel (PTX) plus Cmab is a palliative option after failure of platinum-based therapy, offering overall response rates (ORRs) of 38–55% and median OS of 7.6–10 months (1214). Among others, Hitt et al prospectively showed that PTX and Cmab was active (ORR54%, median PFS 4.2months, median OS 8.1 months) as 1st line treatment in R/M HNSCC patients, for whom platinum is contraindicated (15).…”
Section: Introductionmentioning
confidence: 99%
“…All mice had measurable tumor two weeks after OE19 cell injection. The mice were then randomly grouped (n = 5 per group) and treated intraperitoneally as described earlier with vehicle, nab-paclitaxel (10 mg/kg in 100 μl of PBS, 2 times a week) [34] , paclitaxel (20 mg/kg, 2 times a week for 2 weeks) [35] or carboplatin (50 mg/kg, 2 times a week for 2 weeks) [36] alone and in combinations. The tumor size was measured twice a week for four weeks with slide calipers and tumor volume (TV) was calculated as (W 2 XL)/2, where W is width and L is length of the tumor [37] .…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks after tumor cell injection mice were randomly grouped (n = 5 per group). For mice survival studies mice were treated intraperitoneally as described earlier with vehicle, nab-paclitaxel (10 mg/kg in 100 μl of PBS, 2 times a week) [34] , paclitaxel (20 mg/kg, 2 times a week for 2 weeks) [35] or carboplatin (50 mg/kg, 2 times a week for 2 weeks) [36] alone and in combinations. Animals were examined daily for signs of distress or development of jaundice, and body weight was measured once a week.…”
Section: Methodsmentioning
confidence: 99%